Comprehensive screen the lead and other toxic metals in total environment from a coal-gas industrial city (NW, China): Based on integrated source-specific risks and site-specific blood lead levels of 0–6 aged children. (September 2021) - Cao, Yuhan; Li, Xiaoping; He, Feng; Sun, Xuemeng; Zhang, Xu; Yang, Tao; Dong, Jie; Gao, Yu; Zhou, Qishang; Shi, Danqian; Wang, Jiwen; Yu, Hongtao
Abstract: A new integrated source-specific risk model and site-specific blood lead levels (BLLs) of 0–6 children were introduced to comprehensive understand the status of the toxic metals in soil-dust-plant total environment from a Coal-Gas industrial city, NW China. 144 samples were collected and ten toxic metals (As, Ba, Co, Cr, Cu, Mn, Ni, Sr, Pb, and Zn) were screened by XRF and ICP-MS. It was found that the occurrences of toxic metals deferred in the different medium, such as Co, Cu, Pb, and Zn observed the trend of accumulating in soil and plant compared to clustered distributions of Cr, Mn and Ni preferred to accumulate in dust. However, few bioaccumulations observed in Ulmus pumila L. Toxic metals distributions in majority of sites influenced by coal combustion mixed sources and industrial activities posed the high integrated ecological risks and caused significant non-carcinogenic and carcinogenic integrated risks for local 0–6 children identified by new integrated source-specific risk model, especially observed in the priority contaminants Co and Pb. The site-specific BLLs confirmed that younger children fewer than 4 lived in the north region were more vulnerable to priority Pb pollution as their BLLs above 50 μg/L, almost up to 80 μg/L. Although proportions of source-specific risks to toxic metals changed in soil and dust, the critical sources from coal combustions and industrial activities posed the most important contribution to the local risks. Therefore, effective strategies targeting at critical sources on coal industries should be conducted to reduce risks, and mostly emphasize on the north hotspot areas. Graphical abstract: Image 1 Highlights: New integrated risk model and BLLs of 0–6 children to evaluate the risks of toxic metals in soil-dust-plant. Inventories of toxic metals and critical source in Yan'an are screened. Coal combustion and industrial discharge contributed the high non and carcinogenic risks for 0–6 aged children. Children aged 1–4 years lived in north area are the most sensitive group influenced by priority lead.